(untitled) (Bangladesh Journal of Medical Science, 2016)
Background: The decrease of estrogen level causes atherosclerosis as well as the decline of vascular relaxation ability that, in turns, causes the narrowing of blood vessels lumen. Phytoestrogens give positive effect during the atherosclerosis process and vascular motor tone. Objectives: to find out the effect of isoflavones on the diameter change of hypo estrogenic rats abdominal aortic measured by 12-MHz ultrasound. Materials and Methods: Thirty female rats were divided into 5 groups (n = 6 each) including 1 control group (sham), one ovariectomized (OVX) group, and three test groups. The test rats were OVX group received 0.5 mg/kg BW, 2.5 mg/kg BW and 5 mg/kg BW of isoflavones. Aortic diameter was analyzed in abdominal aorta using ultrasound with 12-MHz linear probes and on histologic specimens. Results: The decreasing of abdominal aortic diameter in all groups shows no significant difference (p>0.05). The measurement using ultrasound does not show any difference compared with that of histologic specimen (p=0.418), with the sensitivity value of 64.7%, specificity of 61.5% and accuracy of 63.3%. Discussion: There is no effect on the giving of isoflavones of several doses during 4-week-period on the diameter of hypo estrogenic rats abdominal aorta. The measurement of rats abdominal aortic diameter using 12-MHz ultrasound is compatible with the measurement on the histologic specimens. Bangladesh Journal of Medical Science Vol.15(4) 2016 p.601-607